3D printing of hydrogel scaffolds for future application in photothermal therapy of breast cancer and tissue repair. (1st July 2019) - Luo, Yongxiang; Wei, Xiaoyue; Wan, Yilin; Lin, Xin; Wang, Zhiyong; Huang, Peng
Graphical abstract: Abstract: Surgical removal remains the main clinical approach to treat breast cancer, although risks including high local recurrence of cancer and loss of breast tissues are the threats for the survival and quality of life of patients after surgery. In this study, bifunctional scaffold based on dopamine-modified alginate and polydopamine (PDA) was fabricated using 3D printing with an aim to treat breast cancer and fill the cavity, thereby achieving tissue repair. The as-prepared alginate-polydopamine (Alg-PDA) scaffold exhibited favorable photothermal effect both in vitro and in vivo upon 808 nm laser irradiation. Further, the Alg-PDA scaffold showed great flexibility and similar modulus with normal breast tissues and facilitated the adhesion and proliferation of normal breast epithelial cells. Moreover, the in vivo performance of the Alg-PDA scaffold could be tracked by magnetic resonance and photoacoustic dual-modality imaging. The scaffold that was fabricated using simple and biocompatible materials with individual-designed structure and macropores, as well as outstanding photothermal effect and enhanced cell proliferation ability, might be a potential option for breast cancer treatment and tissue repair after surgery. Statement of Significance: In this study, a three-dimensional porous scaffold was developed using 3D printing for the treatment of local recurrence of breast cancer and the following tissue repair after surgery. In this approach, easily available materials (dopamine-modified alginate and PDA) with excellent biocompatibility were selected and prepared as printing inks. The fabricated scaffold showed effective photothermal effects for cancer therapy, as well as matched mechanical properties with breast tissues. Furthermore, the scaffold supported attachment and proliferation of normal breast cells, which indicates its potential ability for adipose tissue repair. Together, the 3D-printed scaffold might be a promising option for the treatment of locally recurrent breast cancer cells and the following tissue repair after surgery.